Accumulation of non-compressive fascicular lesions underlies NF2 polyneuropathy - Bäumer, Philipp; Heiland, Sabine; Kästel, Thorsten; Bendszus, Martin; Pham, Mirko (Journal of neurology, 2013)
A distinct polyneuropathy (PNP) syndrome affects up to 66 % of patients with neurofibromatosis II (NF2). Whether this is primarily a diffuse PNP or due to single, surgically amenable mass lesions has not yet been conclusively demonstrated. We aimed to solve this question by investigating the pathomorphological MR imaging correlate of this rare disorder. Eight patients with NF2-PNP were characterized by clinical examination, electrophysiological studies, and genetic analysis. All patients additionally underwent extended peripheral nerve imaging by a novel protocol of large-coverage high-resolution MRI. Quantitative analyses were performed by separately evaluating cross-sectional images, and by categorizing lesions into non-compressive fascicular microlesions (<2 mm), intermediate lesions (2-5 mm), and compressive macrolesions (>5 mm). The predominant imaging findings were non-compressive fascicular microlesions and intermediate lesions. Proximal-to-distal cumulative lesion burden of these lesions correlated strongly with the severity of clinical symptoms of NF2-PNP. In contrast, compressive macrolesions were not found at all in several symptomatic extremities. We conclude that proximal-to-distal accumulation of non-compressive fascicular lesions instead of compressive mass lesions predominantly underlies the clinical manifestation and severity of NF2-associated PNP. Diagnostic management may now be assisted by large-coverage high-resolution imaging of plexus and peripheral nerves. Additionally, the results underscore the feasibility of this new method, which may open up new diagnostic and investigative possibilities for other disseminated disorders of the peripheral nervous system.
Published online: 4 July 2012
Gesehen am 13.11.2018